The Influence of Sales Promotion, FoMO, and Digital Payment on Impulsive Buying in the Digital Era - Saudah Afyana; Willy Abdillah (AIBPM Publisher, 2026)
Digital financial innovations, particularly e-commerce platforms and PayLater services, have significantly reshaped the purchasing habits of Generation Z students by increasing exposure to online shopping convenience, sales promotions, and fear of missing out (FoMO). This study aims to explore the impact of sales promotion and FoMO on impulsive buying behavior, and to analyze the moderating role of PayLater within these relationships. A quantitative approach was employed, using a survey method involving 308 Generation Z students who utilized PayLater services for online purchases. Data were collected using a Likert-scale questionnaire and subsequently analyzed with Structural Equation Modeling (SEM) through SmartPLS. The results reveal that sales promotion (b = 0.201; p = 0.007), FoMO (b = 0.493; p 0.001), and PayLater (b = 0.207; p = 0.001) each demonstrate a positive and significant effect on impulsive buying behavior. Furthermore, PayLater significantly moderates the connection between FoMO and impulsive buying behavior (b = 0.090; p = 0.045), although its moderating effect on the sales promotion-impulsive buying relationship was not supported (b = ?0.033; p = 0.374). These findings suggest that the convenience of digital payment systems might increase impulsive consumption, emphasizing the necessity for improved financial awareness and responsible promotional strategies.